Terminator 3 [videorecording (DVD)] : rise of the machines - Mostow, Jonathan; Schwarzenegger, Arnold; Stahl, Nick, 1979-; Danes, Claire, 1979- (Warner Home Video, 2003)
John Connor is a 20-something living on the streets as a common laborer. His mother has since died, and their earlier efforts did not stop the creation of SkyNet artificial intelligence network. As he will still become the leader of the human resistance, Connor is once again targeted by a Terminator sent from the future by SkyNet. This new Terminator, T-X, is a female and is more powerful than any of her predecessors. To protect Connor, the human resistance sends a new T-101 back from the future.